Connecting with family, friends and others: Informal caregiving among international postgraduate researchers in a British University - Sin, I Lin; Schartner, Alina (Journal of International Students, 2023)
This article casts light on informal caregiving, an essential aspect of the international postgraduate researcher (PGR) experience, but which is often invisible in literature and discourses on international education. Drawing from qualitative semi-structured interviews with international PGRs in a British university, it highlights their dual role as care recipients and lesser known caregivers across transnational and local spaces. It gives insights into the forms and dynamics of care that they give to and receive from family, friends and others, uncovering the emotional and affective aspects of undertaking a postgraduate research degree overseas which impact on their mental wellbeing. The findings have implications for the improvement of university support for international PGRs which has relevance for the wider international student community.